PENGARUH INSTITUTIONAL OWNERSHIP, PROFITABILITAS, LEVERAGE, DAN RELATED PARTY TRANSACTION TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Muhammad Daffa Muthi Fadhali; Herry Laksito (Diponegoro Journal of Accounting, 2023)
This study aims to analyze the factors that influence tax avoidance on manufacturing companies listed on the Indonesia Stock Exchange from 2019-2021. The independent variables used in this study are institutional ownership, profitability, leverage, and related party transaction, while the dependent variable used is tax avoidance. This study uses agency theory to generate testable hypotheses and derive empirical findings from hypothesis testing. The study uses secondary data with a population of 195 manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2021, using purposive sampling to select a sample of 73 manufacturing companies. The multiple linear regression analysis method is used to analyze the data. The results of the study indicate that institutional ownership has a negative and significant effect on tax avoidance, while profitability, leverage and related party transaction have a positive and significant effect on tax avoidance.